The effectiveness of brain-compatible blended learning material in the teaching of programming logic. (December 2016) - van Niekerk, Johan; Webb, Paul
Abstract: Blended learning is an educational approach which integrates seemingly distinct educational approaches, such as face-to-face and online experiences. In a blended learning environment the classroom lectures can, for example, be augmented with learning material offered in a variety of technologically delivered formats. There exist extensive evidence that a blended learning approach which mixes face-to-face and online learning materials is substantially more effective than using only face-to-face educational methods. However, in order to be effective, blended learning course material should still be designed and presented according to sound pedagogical principles. This article presents the results of an experiment to augment the teaching of fundamental programming logic based on the pedagogical principles underpinning brain-compatible learning materials via e-learning delivery mechanisms. The research uses both qualitative and quantitative methods. Results show promise for this use of brain-compatible material in a blended learning context. Highlights: We taught fundamental programming using brain-compatible blended learning material. Qualitative results indicate students prefer this instructional format. Quantitative results indicate an improvement in student learning. Further studies with larger sample sizes could improve practical significance.